REPRESENTATION OF REAL MEN ON TIKTOK : EMIL MARIO CONTENT CONTROVERSY - Fira Firdausiyah; Riska Dewi; Chandrawati A.N; Ari Ade Prasetyo (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Popular culture becomes an arena for identity negotiations, including femininity and masculinity in social spaces. Many people in society have their own views on the issue of femininity and masculinity, so there are various opinions that arise from it. One of them is about the representation of real men who have various opinions from various parties, as discussed by one of Emil Mario's content on tik tok. This study aims to describe real men according to Emil Mario and responses from other parties with different perspectives, such as from the point of view of religion, psychology and ordinary people on this issue. The method used in this research is qualitative using the theory of John W. Creswell. The data was collected by using the observation technique on Emil's video and responses from several other parties, then recording their opinions. The results of this study indicate that there are different points of view because there are many cultural aspects that appear, especially on Tik Tok content.